The development of a surrogate soil to assist the revegetation and stabilisation of metal-mine tailings - HEATHER DE-QUINCEY (2020)
Abandoned mines are considered among the most severe of environmental issues, and are a significant danger to environmental, animal, and human health (Mehta et al., 2020). To date, ~ 600,000 abandoned mines exist, the costly reclamation of which often falls to publicly funded bodies (Archer & Caldwell, 2004; Mayes et al., 2009). Traditional reclamation methods are financially unattainable at ~ £50 million per large mine (McKenna, 2002), and an alternative, lower-cost method is required (Garcia, 2008). One contemporary reclamation method found to be effective is that of capping mine waste with a soil cover (O’Kane & Ayres, 2012). In this research, an adhesive surrogate soil capping layer for the hydraulic application to steep-sided metal-mine tailings was developed at the cost of ~ £6 .m-² (at the time of writing). The surrogate soil was refined throughout a series of trials. A rainfall trial was conducted to develop an adhesive and erosion resistant soil material. A germination trial (N = 500) determined the soil materials which best assisted rapid plant establishment. The successful results of these laboratory-based trials guided a nine-month field trial on an abandoned Pb mine, Nantymwyn (UK) (N = 154). The field trial concluded that the surrogate soils effectively resisted erosion and supported the early (seven month) growth of metal-tolerant grass species. The grasses contained Pb, Zn, Cd and Cu concentrations at < 1% of the phytotoxic threshold. However, seasonal climatic events and a negative water balance ultimately led to complete grass mortality after nine months. Tailings bank destabilisation also influenced grass survival. The research revealed that the soil’s available water supply was of greater impact to plant survival than metal toxicity. The results indicated that should the soils water-holding capacity be improved, the application of a carefully designed surrogate soil has the potential to support vegetative cover on steep, bare metal-mine tailings.